EPISIOTOMY TO RELIEVE DYSTOCIA DUE TO VULVAR STENOSIS AND PERSISTENT HYMEN IN A CROSSBRED COW HEIFER - DALAL, J; SAINI, A; GUNWANT, P; PANDEY, AK; SINGH, g; CHANDOLIA, RK (The Indian Journal of Animal Reproduction, 2016)
Per vaginal examination of a crossbred heifer presented for the treatment of dystocia revealed vulvar stenosis and persistent hymen. Episiotomy followed by excision of transverse band of persistent hymen lead to per vaginal delivery of fetus.
Keywords: Dystocia; Episiotomy; Heifer; Persistent hymen; Vulvar stenosis